The Glu331del mutation in the CYP17A1 gene causes atypical congenital adrenal hyperplasia in a 46, XX female. (2nd December 2017) - Lanzolla, Giulia; Vancieri, Giuseppe; Lanciotti, Silvia; Sangiuolo, Federica; Menegatti, Elisa; Federici, Luca; Moretti, Costanzo; Brancati, Francesco
Abstract: 17α-Hydroxylase deficiency is an uncommon type of congenital adrenal hyperplasia (CAH) caused by mutations in the CYP17A1 gene encoding both 17α-hydroxylase and 17, 20-lyase, essential for sex steroids production. Main clinical features include lack of pubertal development, hypertension, and hypokalemia. We report the first case of a 46, XX female homozygote for the p.Glu331del mutation in the CYP17A1 gene showing an atypical clinical presentation. She was evaluated the first time for primary amenorrhea and delayed puberty in the presence of low levels of androgens, 17β-estradiol, serum cortisol, and high levels of progesterone and gonadotropins. After puberty, the patient did not show hypocortisolism and/or hypertension. She started estrogen therapy for pubertal induction, followed by ethinylestradiol/gestodene with clinical and biochemical stability during the follow-up period. At the age of 40 years, she developed hypokalemia and clinical signs of hypocortisolism. Oral corticosteroid treatment was started showing a prompt clinical improvement. Modeling analysis predicted the main outcome of the E331 deletion to impair cytochrome b5 binding, according to a major effect on the enzyme's lyase activity. These data broaden the molecular and clinical spectrum of CAH caused by 17α-hydroxylase deficiency and adds to current genotype–phenotype correlations.